Request for MEP material for the prototype room of PT2 on ground floor - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the request for MEP material for the prototype room of PT2 on ground floor of BRACU new campus project.